2022
DOI: 10.1007/s00894-022-05355-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DENV NS2B-NS3 protease with active antiviral phytocompounds: structure-based virtual screening, molecular docking and molecular dynamics simulation studies

Abstract: Dengue fever has been a global health concern. Mitigation is a challenging problem due to non-availability of workable treatments. The most difficult objective is to design a perfect anti-dengue agent capable of inhibiting infections caused by all four serotypes. Various tactics have been employed in the past to discover dengue antivirals, including screening of chemical compounds against dengue virus enzymes. The objective of the current study is to investigate phytocompounds as anti-dengue remedies that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Al. [17,26] Our additional research shows that among the phytocompounds listed in Table 6, Glabridin has the highest binding affinity for NS2B/NS3 protease (À 120.122 kJ/ mol). Except this, phytocompounds like Gallocatechin (À 111.168 kJ/mol) and Isorhamnetin (À 105.312 kJ/mol) may play a significant role in the development of rational treatments against DENV NS2B/NS3pro.…”
Section: Binding Free Energymentioning
confidence: 90%
See 3 more Smart Citations
“…Al. [17,26] Our additional research shows that among the phytocompounds listed in Table 6, Glabridin has the highest binding affinity for NS2B/NS3 protease (À 120.122 kJ/ mol). Except this, phytocompounds like Gallocatechin (À 111.168 kJ/mol) and Isorhamnetin (À 105.312 kJ/mol) may play a significant role in the development of rational treatments against DENV NS2B/NS3pro.…”
Section: Binding Free Energymentioning
confidence: 90%
“…Many phytochemicals can be used to treat viral diseases and infections since they have few or no side effects. [14][15][16][17][18][19] From a detailed literature study, eight medicinal plants as shown in S_ Figure : 1 (Vernonia cinerea, Tridax procumbens, Cassia angustifolia, Lawsonia inermis, Dryobalanops aromatic, Punica granatum, Zingiber zerumbet and Zizyphus-jujuba) constituting 82 phytocompounds, which possesses effective antiviral activity against DENV2 have been selected. The effect of V. cinerea leaf extract against DENV NS2B/NS3 protease was investigated through an in vitro viral inhibition assay against Vero cells.…”
Section: Molecular Structure Of the Denv Polyproteinmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] Moreover, the traditional methods of studying binding affinities using MM/PBSA have been largely replaced by the more modern MM/GBSA due to its faster computation speed and slightly higher accuracy. [39] We previously used the MM-PB/GBSA technique to study the SARS-CoV-2 M Pro , [40,41] HIV-1 protease, [42] and DENV NS2B-NS3 protease [43,44] systems. AMBER18's MM-PBSA.py algorithm [45] was used to determine the binding free energies.…”
Section: Mm-gbsa Calculationsmentioning
confidence: 99%